Refinement of ELISA and its use in early detection of coconut root (wilt) disease - M. Sasikala; V. R. Prakash; V. P. Sapna; M. Mayilvaganan; Leena. S. Nair (International Coconut Community Journal, 2005)
Root (wilt) is a major disease of coconut in Kerala and in certain parts of Tamil Nadu. The lasting solution for combating the disease is by evolving root (wilt) disease resistant/tolerant varieties through sustained breeding programmes. Development of visual symptoms of root (wilt) disease is very slow and there is a time lag between infection and symptom expression. Therefore, identification of root (wilt) disease-free palms using early diagnostic techniques (serological techniques) is a basic requirement for the production of quality seedlings. For the mass screening of coconut samples DAC-indirect ELISA has been standardized earlier using antibody raised against pathogen related protein found in diseased palms, but it take about 44 hrs for the completion of the test. In the present investigation using phytoplasma-specific antibodies, test could be refined to make it a more rapid and sensitive one. It has been found that the results could be obtained within 24 hrs with very high sensitivity of 98.4%. Similarly, efficiency of extracting antigen from coconut leaf samples was enhanced by using ART MICCRA D-8 tissue homogeniser. Highest difference in absorbance values between healthy and infected samples was obtained while using carbonate bicarbonate buffer pH 9.6 with additives followed by plain buffer. Thus test could be used to detect phytoplasmal infection in coconut palms even before the appearance of visual symptoms. The modified procedure is being used for identifying disease-free mother palms from disease endemic areas for producing quality seedlings either by crossing programmes or from open pollinated nuts.